THE DEVELOPMENT OF CHILDREN LEARNING ACCORDING TO ITS CHARACTERISTIC (CHILATIC) LEARNING STRATEGY FOR EARLY CHILDHOOD EDUCATION - Betty Yulia Wulansari; Dian Kristiana; Muhibuddin Fadhli (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
The purpose of this research is to develop Children Learning According To Its Characteristic (Chilatic) learning strategy  for early childhood education. This research use RD research method that is supported by qualitative method. The result of this research is the development of Chilatic learning strategy. Chilatic learning strategy is the learning strategy that gives chance to children for getting the learning accompaniment individually by teacher. Syntax of Chilatic learning strategy starts from beginning activity, main activity , and ending activity, in this activity this strategy appear with pattern : 1) Giving explanation about activity , 2) learning contract with student , 3) giving permission to the student for free playing and calling one child for being accompanied individually  in doing the task , 4) if the  child who is being accompanied finish, child is being permitted for playing and call the other children until the end. The benefits of this strategy are easy to be used by teacher, , fulfill the service needs of individual child because the rhythm of children learning understanding is no more than 10 minutes,  know the development of each student in detail , Give free playing to the children without reduce the attention through learning.                                                           Key words: learning strategy, chilatic, early childhood education